Environmental Analysis for Spreading Areas of Scleroderma Disease in Babylon Governorate - Muthik A. Guda (Journal of Global Pharma Technology, 2019)
The aimed of this study is to estimate Scleroderma infections in Babylon Governorate (2016). Locations and number of infected people were detected. The number of infected people reached 17. Those patients were admitted in the government hospitals. A statistical questionnaire was prepared for this study which includes patient's name, gender, age, occupation, address, date of admission to the hospital, date of discharge, and patient's condition. The results of this study found that female' infections were more than males. Scleroderma disease complications caused a change inside immune system, fibrosis, and damage in small blood vessels. It was also found that most of the infections are in Hilla district and less concentrated in the Kefel area. This may be correlated to the population density, lack of health awareness; municipal services, poor infrastructure as well as industrial activities were mostly concentrated inside the city. Further studies related geospatial and environmental variables could help our findings to detect a wide range of patients and related that with site variables.Keywords: Environmental Pollution, Hilla City, Air Pollution, Scleroderma Disease.